Polysome profiling of the plant pathogen response - Hawkes, Alastair (2019)
This study aimed to use a combination of sucrose density gradient centrifugation and RNA-Seq to investigate changes in expression at the transcriptional and translational levels and the differences therein in a susceptible cultivar of Capsicum annuum (pepper) during the early stages of tomato spotted wilt virus (TSWV) infection, a virus that causes significant economic loss in pepper and many other crops and to which there is little robust resistance in the pepper germplasm. Polysome profiles of pepper plants 6 hr after TSWV-inoculation showed a significant increase in polysomally associated material relative to the 80S ribosomal peak and mock- and noninoculated controls, which is indicative of an increase in global translation upon infection. Principle component analysis (PCA) and hierarchical clustering showed that RNA-Seq results for total RNA and pooled polysomal RNA are largely similar but that significant differences were present, which indicates post-transcriptional regulation of expression at the level of translation. Sequencing results also clustered by treatment conditions, showing that expression was significantly affected by TSWV-inoculation. Gene ontology (GO) and KEGG pathway analyses revealed that upon TSWV-inoculation among the genes that reduce in abundance in total and polysomal RNA, there were many involved in promoting pathogen perception, defence signalling, autophagy, and disease resistance. Conversely many genes that were involved in suppressing the pathogen response and maintaining or promoting anabolic processes increase in abundance in total and polysomal RNA, or showed no change in abundance in such a way that may promote susceptibility to TSWV.This study has enhanced the understanding of the compatible reaction between TSWV and pepper by highlighting multiple novel host factors that may be involved in infection. Preliminary optimisation of downstream RNA preparation and QRTPCR demonstrated where methodological changes need to be made in order to enhance reliability of future experiments that build upon the results of this work.